A case of reflux laryngitis after iodine staining for esophageal squamous cell carcinoma - Sho Yatsuji; Yoshitsugu Misumi; Akiko Tamiya; Kouichi Nonaka (DEN Open)
Abstract Iodine staining allows for clear visualization of the lesion boundaries of esophageal squamous cell carcinoma and is used as the gold standard for detecting and diagnosing the extent of the cancer. Heartburn and retrosternal pain are known side effects; however, no reports of pharyngitis or laryngitis exist. Therefore, we present a case of laryngitis caused by iodine reflux. An 80‐year‐old female patient underwent endoscopic submucosal dissection for superficial esophageal cancer. During the operation, a reflux of the iodine used for diagnosing the extent of the lesion occurred, and she experienced laryngitis accompanied by hoarseness postoperatively, which improved with steroid administration. Laryngitis due to iodine reflux may cause airway stenosis, and preventing reflux requires anterograde application of iodine and spraying iodine as gently and locally as possible.